The Impact of Rehabilitation Module of Iran Welfare Organization Among Older Adults - Mohammad Nasiri; Mahshid Foroughan; Vahid Rashedi; Mohammad Reza Shahbazi (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: With the increasing aging population, attention to their problems in society has found vast and new dimensions. The professional rehabilitation teams in day-care centers have aimed at providing services to the elderly to prevent their admission into residential boarding centers. To this end, the Welfare Organization has designed a special service package for the day-care centers. The main objective of this study was to compare the quality of life of older adults in a day center before and after receiving the rehabilitation module of the Welfare Organization. Methods & Materials: This is a descriptive-analytic study with 2 groups and pretest/posttest design. The study population consisted of all older adults referred to day-care centers for older adults. The study sample comprised 50 older adults in the Kahrizak Rehabilitation Center No.2, located in Mohammad Shahr Karaj, Iran in 2014-2015. They were selected through the convenient sampling method and by following the inclusion criteria. They were randomly allocated to the experimental and control groups with 25 older adults in each group. To observe the research ethics, the control group was put on the waiting list for receiving the services. The research instruments included SF-36 quality of life and demographic questionnaires. The SF-36 questionnaire was implemented before, 1 month, and 3 months after receiving the services in both groups. The data were analyzed using SPSS-20. Data analysis was performed using 1-way ANOVA with repeated measures. Results: In this study, the mean age of the control and experimental groups were 66.43 and 68.1 years, respectively. T-test showed that there was no significant difference between the control and experimental groups with regard to their ages (P=0.722). Furthermore, there were no significant differences between 2 groups with regard to sex, education degrees, and history of hospitalization. The mean scores of quality of life in the intervention group at baseline, 1 month and 3 months after the study were 43.95, 56.30, and 74.38, respectively. The values for the same parameters in the control group were 44.74, 49.79, and 57.82, respectively. The lowest score in the quality of life questionnaire was 24.72, and the highest was 86.11. In addition, there was no significant difference between 2 groups with regard to mean scores of their quality of life at baseline; however, there were significant differences for 1 and 3 months after the study (respectively, P<0.001, P<0.015). Conclusion: The results showed that the day-care services significantly increased the quality of lives of older people. Therefore, it is hoped that these services can be used along with other conventional services as an effective method. Furthermore, the non-pharmaceutical interventional module can be used in promoting the quality of lives of older people. Rehabilitation services designed by the Welfare Organization for use in the day-care centers for older adults have a positive impact on the elders' quality of lives, and it can be considered as an efficient intervention in rehabilitating older adults.